INFLUENCE OF KETOSIS AND GLYCEMIA LEVELS ON CRAVING FOR ETHANOL IN ALCOHOLIZED RATS - T.I. Panova; O.I. Myronenko (Медична наука України, 2022)
Relevance. In case of developed alcoholic disease, under conditions of alcoholic hypoglycemia, ketone bodies act as an energy substrate for the brain. However, the role of ketone hunger for maintaining the craving for alcohol has not been established. The assumption of such a connection has a right to exist, since it is alcohol that stimulates the formation of ketone bodies. Therefore, with developed alcoholism, the desire to consume alcohol (and, in fact, "saturate" the brain with ketone bodies) can be considered as a consequence of hypoketonemia. Accordingly, the hunger of the alcoholic is the result of hypoketonemia, but not hypoglycemia. Therefore, it is relevant to conduct a study in which the given variables (controlled by us) were the level of glycemia and the level of ketonemia, and the amount of alcohol consumed voluntarily (under conditions of free choice) was a derivative and dependent value.